ECONOMIA CIRCULARĂ – STRATEGIA SUSTENABILĂ ZERO DEȘEURI PENTRU REPUBLICA MOLDOVA - Rusu, Elena (CEP USM, 2022)
This article aims to trace the circularity of waste from collection to recycling, but also to identify best practices in the organization of selective waste collection, as well as existing intelligent solutions that will allow the optimisation of processes within the waste management system. The presented material is intended for academics, institutions, environmental organizations and all those interested in the circular economy and waste collection processes.
Keywords: circular economy; waste management; energy conservation; biodiversity education; climate change